Gas-assisted electrospinning of high-performance ceramic fibers: Optimal design modelling and experimental results of the gas channel of the nozzle - Xu, Guojie; Chen, Mingyi; Gao, Yufei; Chen, Ying; Luo, Zhifeng; Wang, Han; Fan, Jie; Luo, Jie; Ou, Weicheng; Zeng, Jun; Zhu, Ziming; Chen, Rouxi (Frontiers in Materials, 2023)
Electrospinning (ES) of ceramic fiber has mostly remained in the research level, which can be basically because of hard process and parameters controlling and the low rate of production. The yield of fiber production by solution blow spinning (SBS) is exciting but the production process is unstable due to reverse flow phenomenon. In this paper, we prepared high-performance ceramic fibers by gas-assisted electrospinning (GES), which combined the advantages of ES and SBS. And we provided a comprehensive numerical and experimental analysis for nanofibers produced using GES. The gas flow characteristics through different parameters' nozzle were investigated numerically using computational fluid dynamics and experimentally in a custom-built gas-assisted electrospinning setup to produce SiO2 nanofibers.